2012
DOI: 10.1136/vr.e2366
|View full text |Cite
|
Sign up to set email alerts
|

Update on cattle health schemes in the UK

Abstract: Update on cattle health schemes in the UK I WOULD like to update colleagues on the position with the Cattle Health Certification Standards (CHeCS)-accredited schemes. Booth and Brownlie (2011), in their recent informative paper on establishing a pilot bovine viral diarrhoea virus (BVDV) eradication scheme in Somerset, quoted a personal communication with me in 2007 that only 4.4 per cent of UK farms were members of CHeCS-accredited schemes. This itself was a major improvement on the figure quoted by Burr (2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…An idea of the scale of this ‘missing’ data can be obtained from a recent estimate of the coverage of herd health schemes in GB. It has been estimated that approximately 14,000 cattle herds (around 14 per cent of UK holdings) have some form of disease surveillance within a herd health scheme, with the likely dairy:beef split being around 40:60 (Brigstocke 2012). Limited epidemiological data from these schemes appears to be publicly available.…”
Section: Discussionmentioning
confidence: 99%
“…An idea of the scale of this ‘missing’ data can be obtained from a recent estimate of the coverage of herd health schemes in GB. It has been estimated that approximately 14,000 cattle herds (around 14 per cent of UK holdings) have some form of disease surveillance within a herd health scheme, with the likely dairy:beef split being around 40:60 (Brigstocke 2012). Limited epidemiological data from these schemes appears to be publicly available.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004 approximately 1% of UK herds were in a CHeCS scheme and an estimated 4.4% in 2007. In 2012 it was reported that 13 500 to 14 000 UK herds had some form of disease monitoring, control and/or eradication under a CHeCS-accredited scheme -approximately 14% of UK cattle holdings (Brigstocke, 2012). The majority of producers engaged with CHeCS at this time were screening for BVDV.…”
Section: Switzerlandmentioning
confidence: 99%